Low Circulating 25-Hydroxyvitamin D Concentrations Are Associated with Defects in Insulin Action and Insulin Secretion in Persons with Prediabetes. Issue 4 (4th March 2015) - Abbasi, Fahim; Blasey, Christine; Feldman, David; Caulfield, Michael P; Hantash, Feras M; Reaven, Gerald M
Abstract: Background: Individuals with prediabetes mellitus (PreDM) and low circulating 25-hydroxyvitamin D [25(OH)D] are at increased risk of type 2 diabetes mellitus (T2DM). Objective: We aimed to determine whether low 25(OH)D concentrations are associated with defects in insulin action and insulin secretion in persons with PreDM. Methods: In this cross-sectional study, we stratified 488 nondiabetic subjects as having PreDM or normal fasting glucose (NFG) and a 25(OH)D concentration ≤20 ng/mL (deficient) or >20 ng/mL (sufficient). We determined insulin resistance by steady state plasma glucose (SSPG) concentration and homeostasis model assessment of insulin resistance (HOMA-IR) and insulin secretion by homeostasis model assessment of β-cell function (HOMA-β). We compared insulin resistance and secretion measures in PreDM and NFG groups; 25(OH)D-deficient and 25(OH)D-sufficient groups; and PreDM-deficient, PreDM-sufficient, NFG-deficient, and NFG-sufficient subgroups, adjusting for age, sex, race, body mass index, multivitamin use, and season. Results: In the PreDM group, mean SSPG concentration and HOMA-IR were higher and mean HOMA-β was lower than in the NFG group ( P < 0.001 for all comparisons). In the 25(OH)D-deficient group, mean SSPG concentration was higher ( P < 0.001), but neither mean HOMA-IR nor HOMA-β was significantly different from that in the 25(OH)D-sufficient group. In the PreDM-deficient subgroup, mean (95% CI) SSPG concentration was higher ( P < 0.01) than in the PreDM-sufficient, NFG-deficient, and NFG-sufficient subgroups [192 (177–207) mg/dL vs. 166 (155–177) mg/dL, 148 (138–159) mg/dL, and 136 (127–144) mg/dL, respectively]. Despite greater insulin resistance, mean HOMA-β was not significantly higher in the PreDM-deficient subgroup than in the PreDM-sufficient, NFG-deficient, and NFG-sufficient subgroups [98 (85–112) vs. 91 (82–101), 123 (112–136), and 115 (106–124), respectively]. Conclusion: Subjects with PreDM and low circulating 25(OH)D concentrations are the subgroup of nondiabetic individuals who are the most insulin resistant and have impaired β-cell function, attributes that put them at enhanced risk of T2DM.